2011
DOI: 10.1089/pho.2009.2680
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial on the Effect of Low-Level Laser Therapy on Chronic Diabetic Foot Wound Healing: A Preliminary Report

Abstract: The study provides evidence that LLLT can accelerate the healing process of chronic diabetic foot ulcers, and it can be presumed that LLLT may shorten the time period needed to achieve complete healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 28 publications
2
107
1
9
Order By: Relevance
“…A double-blind clinical trial [42] also confirmed accelerated reduction of ulcer size and larger number of patients with complete healing in the group who received laser therapy. Heliumneon and infra-red laser therapy of diabetes-related skin lesions improved blood flow parameters compared with patients who had only received conventional treatment [43].…”
Section: Laser Therapymentioning
confidence: 75%
“…A double-blind clinical trial [42] also confirmed accelerated reduction of ulcer size and larger number of patients with complete healing in the group who received laser therapy. Heliumneon and infra-red laser therapy of diabetes-related skin lesions improved blood flow parameters compared with patients who had only received conventional treatment [43].…”
Section: Laser Therapymentioning
confidence: 75%
“…Wound size was significantly reduced at week 4 in the low-level laser therapy compared with the placebo group, and at week 20 eight patients in the treatment group and only three in the placebo group achieved complete wound healing. The mean duration until complete wound healing was not statistically significant: week 11 in the treatment group compared to week 14 in the control group [54] . These limited data suggest there may be a role for low-level laser therapy in accelerating healing of diabetic foot ulcers wound.…”
Section: Electrotherapy Methodsmentioning
confidence: 68%
“…Presumably this was related to the increased skin blood circulation and contributed to improved healing [53] . In another randomized controlled trial of patients with a diabetic foot ulcer, 13 received lowlevel laser therapy and 10 patients were in a placebo group [54] . Wound size was significantly reduced at week 4 in the low-level laser therapy compared with the placebo group, and at week 20 eight patients in the treatment group and only three in the placebo group achieved complete wound healing.…”
Section: Electrotherapy Methodsmentioning
confidence: 99%
“…In addition to increased MMP-9, other studies have also found increased levels of MMP-2 and -8 [4][5][6]. PBM has been shown to stimulate cells and wound healing, and has aided in the healing of chronic diabetic ulcers [8][9][10][11][12][13]. Aparecida Da Silva and co-workers irradiated diabetic induced male Wistar rats (660 nm, 4 J/cm2) and evaluated MMP-2 and -9, and Type I and III collagen 24 h post-irradiation [25].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to an increase in adenosine triphosphate (ATP) which in turn activates a cascade of intracellular signals and messengers, leading to various down-stream effects such as increased proliferation, cellular migration and viability, collagen production, as well as gene transcription [8]. There are several research papers which demonstrate the beneficial effect of PBM in the treatment of diabetic ulcers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%